Morpho-physiological characterization of germination in Senna siamea - Eudes da Silva, Francisco; Dias Pereira, Márcio; Patrícia Balduíno Nicolau, Josefa; Cardoso Felix, Francival; Carlos da Silva Santos, Gean; Karine Pereira de Araújo, Jayane; da Silva Alves Almeida, Robevania; de Lucena Alcântara Bruno, Riselane (Revista Ciência Agronômica, 2022)
Establishing the appropriate procedures for conducting germination tests in forest species is important for marketing the seeds, especially species that are not yet included in the relevant Normative Instructions. The aim of this study was to determine the ideal conditions of temperature and substrate to carry out the germination test on seeds of Senna siamea, as well as: (i) to characterise the morpho-physiology of seedling establishment, (ii) the period for seedling evaluation, and (iii) validate the efficiency of the methodology in 10 batches of seeds. The experimental design was completely randomised in a 2 x 2 factorial scheme (temperatures x substrates), with 12 replications of 50 seeds in each treatment. To evaluate the different batches, the data were submitted to analysis of variance, and the mean values compared by the Scott-Knott test at 5% probability. The percentage and speed of germination, first count, seedling length, accumulated germination, and seedling morphology were evaluated. The germination potential of S. siamea seeds is greater on paper-roll substrate at temperatures of 25 °C and 30 °C (86% and 87%). The first germination count and final seedling evaluation should be carried out 15 and 21 days after sowing, respectively. The species has epigeal germination and the seedlings are phanerocotyledonous. It was found that the method for carrying out and evaluating the germination test recommended in this study is suitable for evaluating batches of S. siamea seeds.